2005
DOI: 10.1074/jbc.m501645200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Localization and Identification of a Critical Aspartate Suggest Non-redundant Proteolytic Functions of the Presenilin Homologues SPPL2b and SPPL3

Abstract: Signal peptide peptidase (SPP) is an unusual aspartyl protease that mediates clearance of signal peptides by proteolysis within the endoplasmic reticulum (ER). Like presenilins, which provide the proteolytically active subunit of the ␥-secretase complex, SPP contains a critical GXGD motif in its C-terminal catalytic center. Although SPP is known to be an aspartyl protease of the GXGD type, several presenilin homologues/SPP-like proteins (PSHs/SPPL) of unknown function have been identified by data base searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 49 publications
7
114
1
Order By: Relevance
“…We also found that the N-terminal half is sufficient for the tetrameric assembly of SPP, although the precise mode of interaction still remains unknown. However, SPP/ SPPL proteins were never cofractionated with other member proteins of the SPP family (19,31), suggesting a specific mechanism of recognition and interaction behind homo-oligomerization. Very recently, 200-, 400-, and 600-kDa complexes containing SPP and its substrates were reported, in accordance with our results (46).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We also found that the N-terminal half is sufficient for the tetrameric assembly of SPP, although the precise mode of interaction still remains unknown. However, SPP/ SPPL proteins were never cofractionated with other member proteins of the SPP family (19,31), suggesting a specific mechanism of recognition and interaction behind homo-oligomerization. Very recently, 200-, 400-, and 600-kDa complexes containing SPP and its substrates were reported, in accordance with our results (46).…”
Section: Discussionmentioning
confidence: 99%
“…S1A) (22,40), suggesting that the ability of SPP to form a homo-oligomer is conserved beyond species irrespective of the formation of SDS-resistant dimer. In addition, DDM-solubilized SPPL2b, of which the mature form migrated at 90 kDa on SDS-PAGE (19), was detected at 400 kDa on BN-PAGE (supplemental Fig. S1, B and C).…”
Section: Proteolytically Active Spp Polypeptides Form a Multimericmentioning
confidence: 99%
See 2 more Smart Citations
“…Its activity is required for histocompatibility antigen E (HLA E) epitope formation (28); maturation of hepatitis C virus (29); and, in zebrafish, neuronal cell survival (30). Like presenilin, SPP can be photolabeled by a ␥-secretase transition state analog inhibitor, indicating conservation of active-site structure within the two enzymes (31,32).…”
mentioning
confidence: 99%